Marketing and Innovation Process in Agri-Food Companies: Analysis via the Stage-Gate Model - Hakima SOUKI; Sabrina BOUKELLAL; Mohand CHITI (Management and Economics Review)
The uncertainty that characterises the development of new products has become one of the major concerns of management professionals and researchers. A new marketing approach focusing on the synergy between creativity, innovation, and marketing skills has underlined the importance of marketing efforts in the success of new products throughout the innovation process. In this article, we highlight the innovation process adopted by agri-food companies by examining the deployment of marketing activities in their innovation process. For this purpose, we adopted the „Stage-Gate System” (SGS) model developed by Cooper et al. (2016), a proven method for managing product development projects in the manufacturing sector. In addition, by mobilising dependency and influence matrices, we situate the place given to marketing in the new product development process while emphasising the importance of cross-functional collaboration. To carry out this research, we opted for a qualitative exploratory method at six companies, and we used a triangulation of analysis methods: content analysis, cognitive content analysis, and processual analysis. For the modelling of process mapping, we drew inspiration from the Stage-Gate System innovation process model. The stages of the innovation process and the theoretical links identified in the SGS model are confirmed by the findings of the empirical study, except that economic profitability and cost optimisation take precedence over the needs of target customers, which may restrict the success of the new product launch.